Experimental Investigation of Thermal Runaway Behavior and Hazards of a 1440 Ah LiFePO4 Battery Pack - Hao Chen; Kai Yang; Youwei Liu; Mingjie Zhang; Hao Liu; Jialiang Liu; Zhanzhan Qu; Yilin Lai (Energies, 2023)
The thermal runaway (TR) behavior and combustion hazards of lithium-ion battery (LIB) packs directly determine the implementation of firefighting and flame-retardants in energy storage systems. This work studied the TR propagation process and dangers of large-scale LIB packs by experimental methods. The LIB pack consisted of twenty-four 60 Ah (192 Wh) LIBs with LiFePO4 (LFP) as the cathode material. Flame performance, temperature, smoke production, heat release rate (HRR), and mass loss were analyzed during the experiment. The results indicated that TR propagation of the LIB pack developed from the outside to the inside and from the middle to both sides. The development process could be divided into five stages corresponding to the combustion HRR peaks. In the initial stages, the main factor causing LFP battery TR under heating conditions was the external heat source. With the propagation of TR, heat conduction between batteries became the main factor. Hazard analysis found that the HRRmax of the LIB pack was 314 KW, more than eight times that of a single 60 Ah battery under heating conditions. The LIB pack had higher normalized mass loss and normalized THR (6.94 g/Ah and 187 KJ/Ah, respectively) than a single LFP battery. This study provides a reference for developing strategies to address TR propagation or firefighting in energy storage systems.